Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1074/mcp.t100006-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Protein Subpopulations Undergoing Protein-Protein Interactions

Abstract: A new method is described for isolating and identifying proteins participating in protein-protein interactions in a complex mixture. The method uses a cyanogen bromideactivated Sepharose matrix to isolate proteins that are non-covalently bound to other proteins. Because the proteins are accessible to chemical manipulation, mass spectrometric identification of the proteins can yield information on specific classes of interacting proteins, such as calcium-dependent or substrate-dependent protein interactions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In a previous report (Nelson et al, 2002), we showed that by eluting the bound proteins with EGTA instead of urea, the selection method can be used to screen for calcium-dependent protein interactions. Of 12 proteins identified in this earlier study, 8 were either known calcium-binding proteins or proteins with known calcium-dependent protein interactions, indicating that the method was capable of enriching a subpopulation of proteins from a complex mixture on the basis of specific interaction criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous report (Nelson et al, 2002), we showed that by eluting the bound proteins with EGTA instead of urea, the selection method can be used to screen for calcium-dependent protein interactions. Of 12 proteins identified in this earlier study, 8 were either known calcium-binding proteins or proteins with known calcium-dependent protein interactions, indicating that the method was capable of enriching a subpopulation of proteins from a complex mixture on the basis of specific interaction criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Even methods used for large-scale functional genomics, such as the yeast two-hybrid system (Fields and Song, 1989;Schwinkowski and Fields, 2000;Uetz et al, 2000) and phage display (Smith, 1985;Rossenu et al, 1997), cannot be adapted to search for protein interactions that occur as a physiological response in specialized tissues because of their reliance on single-celled organisms and cloned proteins. Therefore, we used a novel separation method (Nelson et al, 2002) to isolate a subpopulation of proteins that participates in protein-protein interactions. This permitted the identification of 16 proteins exhibiting heretofore unknown memory-specific changes in protein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…For those, LC/MS/MS analysis was performed as described previously [65]. The resulting tandem mass spectra were extracted using BioWorks v3, and the MS/MS spectra were analyzed by both Mascot (version 2.3; Matrix Science, London, UK) [64] and X!…”
Section: Methodsmentioning
confidence: 99%
“…The spots observed to be different between the normal versus the mutant pull-downs were identified by MS. Fifteen proteins that interacted with the C-terminal tail of the receptor were observed. A method, based on cyanogens bromide-activated Sepharose matrix, was developed by Nelson et al (191) for isolating interacting proteins. In this method, activated Sepharose is added to bind 50% of the proteins present in a mixture.…”
Section: Functional Proteomicsmentioning
confidence: 99%